Tren Riset Pelanggaran HAM Berat: Analisis Bibliometrik dan Agenda Riset Masa Depan - Santoso, Iwan; Jeddawi, Murtir; Sahyana, Yana; Arsyad, Romli; Alma'arif, Alma'arif (Jurnal HAM, 2023)
This study aims to analyze research trends related to human rights, identify countries, organizations, and authors who contribute significantly to the aforementioned research. Furthermore, this paper identifies related articles that strongly influence these scientific publications. VosViewer collects data from Scopus Database Journal and analyzes it using bibliometric analysis. As a result of the study, the United States has the highest number of publications. Furthermore, the Department of Epidemiology at the Johns Hopkins Bloomberg School of Public Health in Baltimore, Maryland, is the organization that has focused the most attention and influence on the issue of resolving gross human rights violations. Aside from that, Professor C. Beyrer of the United States is the most prolific and influential researcher on the topic of resolving gross human rights violations. Bibliometric analysis and content analysis show that the trend of resolving gross human rights violations in several countries since 2015 has been more toward resolution with non-judicial mechanisms. However, the results of the research show that several relevant articles do not provide a clear definition of gross human rights violations. Therefore, further research from other databases, such as the Web of Science, is required.